2008
DOI: 10.2174/1874838400801010005
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy in Children with Asthma: Prevalence and Correlation with Clinical Severity of Respiratory Disease

Abstract: Epidemiological evidence suggests that there is a link between asthma and food allergy. The aim of this study was to estimate the prevalence of food allergy in asthmatic children and to evaluate a possible impact of food allergy on asthma severity. The study enrolled 103 asthmatic children (mean age: 11 years). Skin prick-test, dosage of specific IgE to a standardized panel of inhalant and food allergens and spirometric evaluation was made for each patient. Twenty-four (23%) patients presented food allergy, 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 37 publications
5
11
1
1
Order By: Relevance
“…Previous studies have shown that the incidences of FA in asthmatic children range from 4% to 44%. 4 34 36 37 38 39 A high incidence of FA in certain studies may result from methodological differences in diagnosis: FA was diagnosed only on the basis of results of the history or sIgE levels above a 95% positive predictive value, while in our study FA was diagnosed on the basis of DBPCFC results.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Previous studies have shown that the incidences of FA in asthmatic children range from 4% to 44%. 4 34 36 37 38 39 A high incidence of FA in certain studies may result from methodological differences in diagnosis: FA was diagnosed only on the basis of results of the history or sIgE levels above a 95% positive predictive value, while in our study FA was diagnosed on the basis of DBPCFC results.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have indicated that the incidence of sensitization to food allergens in asthmatic children varies between 29.3% and 77%. 37 38 39 The lower sensitization rate noted in this study may be due to older age, less frequent occurrence, or the presence of another phenotype of FA in Poland.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The secondary form occurs more frequently [1, 6–9, 11, 18, 40, 41]. Although the provocation tests with foods are not always performed routinely, they may be considered to be the definite confirmation of involvement of particular foods in the patient's complaints [1–13, 18, 20, 22, 25, 27, 28, 40, 4251].…”
Section: Introductionmentioning
confidence: 99%